Effect of Antiviral Drugs against Cervid Herpesvirus 2 (CvHV2) in vitro - Magnuson, Emily Elizabeth (UiT Norges arktiske universitet, 2018)
Cervid herpesvirus 2 (CvHV2) is an alphaherpesvirus found in Rangifer subspecies throughout most of the circumpolar Arctic and the causative agent of infectious keratoconjunctivitis (IKC) in semi-domesticated Eurasian tundra reindeer (Rangifer tarandus tarandus). IKC occurs as regular outbreaks, affecting dozens of reindeer in a herd, and is most common and severe among calves and young animals. IKC often appears as mild clinical signs from which the animals often recover, but the disease can progress to more advanced stages where the eye is severely damaged, resulting in blindness or death. Development of an antiviral therapy for CvHV2 could improve animal welfare conditions and reduce economic losses within reindeer herding industry in Fennoscandia. To our knowledge, only one pilot study has previously tested the effectiveness of antiviral drugs against CvHV2 and indicated that the nucleoside analog drug Acyclovir, commonly used as an antiherpetic treatment in humans and other species, was not successful inhibiting viral replication. This master’s study aimed to further investigate the effect of antiviral drugs against CvHV2 by testing Ganciclovir and Cidofovir, and to evaluate their potential use as part of a treatment for IKC in semi-domesticated reindeer in Fennoscandia. An in vitro experiment which used Madin-Darby bovine kidney (MDBK) cell cultures was used as a preliminary model for natural CvHV2 infection in reindeer. A negative dose-response relationship was found for both Ganciclovir and Cidofovir, however, neither drug was able to completely inhibit the viral replication even at the highest drug concentrations and lowest viral titers tested. These findings indicate that both drugs are tentative candidates for the development of an antiviral treatment for CvHV2, but further studies to attempt to increase the therapeutic index of either drug should be strongly considered before testing in live animals.